Marcadores moleculares forenses como ferramenta no estudo de alterações na herança do cromossomo 21 - Cavalheiro, Camila Pivetta (2019)
Somatic numeric chromosomal alterations are associated with non-disjunction of chromosomes or sister chromatids during gametogenesis or during the early postzygotic phase. The rescue of monosomies or trisomies is a classic cellular mechanism, poorly understood, that, via chromosome pairing, allows the cell to return to disomy. Random pairing can, however, maintain in the individual disomic pairs from only a single parent, which may follow a phenotypic development compatible with normality. The uniparental disomy (UPD) corresponds precisely to this type of alteration, that is, the descendant presents, for one of the chromosomal pairs, the contribution of only one of his parents. Despite being a well-recognized chromosomal alteration in clinical human genetics, in the forensic context the occurrence of UPD has been little considered to explain allelic inconsistencies in kinship analysis. Considering paternity investigation cases that report inconsistencies, there is a real possibility that at least a fraction of them are not caused by slippage events, but rather by UPD chromosomal abnormalities. We report here the investigation of a paternity case (mother, child and alleged father), who’s the inconsistencies between the obligatory paternal alleles (OPA) and the alleged father alleles may be explained by the occurrence of maternal uniparental isodisomy of chromosome 21 (imUPD-21) was 2.56 billion times greater than the chance of being explained by the occurrence of slippage mutation. A total of 350 short tandem repeats (STR) markers and single nucleotide polymorphisms (SNP) markers were tested, allowing a statistical conclusion with a LR = 2.56x1040 of true biological linkage between the trio, despite eight inconsistencies detected between the OPA and the father's alleles. In addition, in this paper we reviewed over 100,000 paternity investigation cases looking for inconsistencies on chromosome 21, which could also be explained by the UPD. In conclusion, it is considered that similar investigations may have improved statistics if the occurrence of classical chromosomal alterations is considered when formulating the hypotheses.